An Evaluation of Bureaucratic Reform in Improving Public Service Quality at the Surabaya District Attorney’s Office: Evaluasi Reformasi Birokrasi dalam Meningkatkan Kualitas Pelayanan Publik di Kejaksaan Negeri Surabaya - Hayyuisman, Asterisk; Kamariyah, Sri; Mustofa, Amirul (Universitas Muhammadiyah Sidoarjo, 2025)
This study examines the implementation of bureaucratic reform at the Surabaya District Attorney’s Office and its influence on public service quality. Bureaucratic reform is considered a strategic initiative to promote more effective, efficient, and accountable service delivery. However, its application in the law enforcement sector still faces several barriers, including inconsistent procedures and limited institutional capacity. The main objective of this research is to assess the relationship between bureaucratic reform and public service quality and to identify the reform dimensions that most significantly contribute to service improvement. The study applies a quantitative explanatory design through a survey of 80 respondents, comprising 15 staff members and 65 service users. Data were analyzed using descriptive statistics, validity and reliability testing, Pearson correlation, and simple linear regression. Service quality was measured using the SERVQUAL framework, which includes tangibles, reliability, responsiveness, assurance, and empathy. The findings reveal a positive and statistically significant relationship between bureaucratic reform and public service quality (r = 0.712; p < 0.05). Bureaucratic reform accounts for 50.7% of the variation in service quality, with transparency and procedural efficiency identified as the strongest predictors. The study recommends strengthening institutional structures, enhancing employee capacity, and adopting technological innovations to ensure more consistent implementation of reform and to foster responsive, sustainable public services.